Research and development of the sOLVe Tube™ dual lumen endobronchial tube: from concept to construct - Nwajuaku, Patricia; Barjaktarevic, Igor; Hoftman, Nir (Frontiers in Medical Technology, 2023)
Funding for the research herein described came from the UCLA Department of Anesthesiology and Pain Management. Intellectual property (US and international patents) obtained during development of this product (sOLVe Tube TM ) are owned by the University of California and licensed to the start-up company HyTek Medical. Author Nir Hoftman is an inventor of the device and a founder and shareholder of HyTek Medical. Authors Patricia Nwajuaku and Igor Barjaktarevic have no affiliation to HyTek medical and no conflicts of interest to disclose. INTRODUCTION Lung isolation and one lung ventilation (OLV) are surgical and anesthesia techniques frequently used in thoracic surgery and other specialized clinical scenarios. Thoracic surgeons in the United States perform approximately 530,000 operations per year to address diseases of the lungs, trachea, esophagus, chest wall, mediastinum, and diaphragm, and many of these require lung isolation and OLV. 1 There are approximately 4,000 cardiothoracic surgeons in the United States who also perform minimally invasive heart surgery that utilizes similar surgical exposure techniques. 2 OLV is a critical step in creating suitable conditions for thoracic surgery. 3 This technique enables one lung to ventilate and oxygenate the patient while the other lung is collapsed and immobilized, facilitating surgery of the chest and/or its contents. Surgery on the lung itself requires the organ to be non-ventilated in most cases, especially in minimally invasive and robotic surgery. 4-9 Furthermore, other operations in the chest including heart, esophagus, and spine procedures require lung collapse to enable surgical exposure and proper visualization of those structures. 10,11 . Finally, OLV provides containment of unilateral pulmonary bleeding or infection, management of bronchopleural fistula or other unilateral pulmonary air leaks, and differential lung ventilation in the critical care setting.Current routine practice techniques to achieve one lung ventilation include utilization of a bronchial blocker via a single lumen tube or a double lumen endobronchial tube (DLT). OLV is most commonly achieved by use of the DLT, however, due to their shape and size, they can be difficult to pass through the larynx, and are more likely to cause oropharyngeal or tracheal injury than a single lumen tube.